Desenvolvimento de uma tinta condutora a base d’água a partir de amido e materiais de carbono para confecção de eletrodos impressos descartáveis para sensoriamento e biossensoriamento - Freitas, Rafaela Cristina de (2025)
Screen-printed electrochemical sensors have attracted interest in recent years due to advantages such as reduced cost, ease of use and production, reduced sample volume for analysis and the possibility of miniaturization, and can be practical and produced on a large scale. For this, the use of conductive inks is essential in the manufacturing process of these devices, since the development of a new water-based ink emerges as a sustainable and environmentally friendly alternative, due to the non-use of organic solvents. In this line, the search for new sustainable materials is growing, due to the concern with the increasing disposal of waste. Thus, biopolymers have been highlighted in use in several areas of the industry due to their film-forming capabilities, low toxicity, biodegradability and relatively low cost, where we can highlight amide present in tapioca as a binder to be used in the use of inks. Therefore, in this dissertation, a new formulation of water-based conductive ink was developed, using tapioca, graphite 35% (w/w) and carbon black 10% (w/w), which includes into the concept of the green index metric. From this ink, it was possible to apply to the manufacture of disposable screen-printed electrodes through screen printing, with the devices being used in the determination of uric acid by the differential pulse voltammetry technique, in a linear range of 5.0 to 100 mol L−1 and a limit of detection (LOD) = 0.34 mol L−1. Using the same screen-printed electrode, an electrochemical biosensor was developed with the addition of green coconut fiber to the conductive ink formulation, due to the presence of peroxidase enzyme. Thus, with the biosensor, an analytical curve for hydrogen peroxide was obtained with linear range of 2.3 to 11.4 mmol L−1 with a LOD = 0.61 mmol L1, using the cyclic voltammetry technique. Therefore, in this dissertation it was possible to develop a new and more sustainable water-based conductive ink, as well as its application in the manufacture of screen-printed electrodes, for sensing and biosensing, through the modification of the ink with coconut fiber.